Matter and energy - Silva , José Augusto Ribeiro da; Menezes , Maria Ângela de B. C.; Neto , Aimoré Dutra (Physicae Proceedings, 2020)
Nuclear energy is a typical example of the application of the equivalence between matter and energy. In nuclear fission and fusion reactions, when the total mass of the products is lower than that of the reactants, energy is released according to E = mc^2 . This energy is released via photons, as explained by the Planck relation, E = h f , which is based on undeniable experimental evidence. Much has been discussed about conversion of energy to matter, but the nature of this process remains mysterious. This paper presents a theoretical study that shows that a system possessing electromagnetic energy has inertia corresponding to the relativistic equivalent (mass) on the basis of its momentum and the Doppler effect. When this system undergoes translation, its space energy changes. This phenomenon follows a wave standard similar to that observed one for free particles.